Analysis of ALDH1A1 and ALDH1A3 Gene mRNA Expressions in Adipose-Derived Stem Cells (ASCs) and Umbilical Cord Stem Cells (UCSCs) - Septelia Inawati Wanandi; Purnamawati Purnamawati; Alice Tamara; Karina Teja Putri; Daniel Marcellius Simadibrata (The Prodia Education and Research Institute (PERI), 2018)
BACKGROUND: ALDH1A1 and ALDH1A3, the most renowned isozymes of aldehyde dehydrogenase (ALDH)1, are important in regulating the pluripotency of human mesenchymal stem cells (MSCs) and cancer stem cells (CSCs). The study aimed to analyze the mRNA expression of ALDH1A1 and ALDH1A3 genes in adipose stem cells (ASCs) and umbilical cord stem cells (UCSCs) along with their correlations to Oct-4 mRNA expression. Additionally, the interaction between these proteins was also investigated using in silico study to confirm the pluripotency of both MSCs compared to human breast ALDH+ CSCs.METHODS: This research focused on determining mRNA levels of ALDH1A1, ALDH1A3 and Oct-4 in ASCs and UCSCs using one-step qRT-PCR. The data were then normalized to those in human breast CSCs and 18S rRNA. Oct-4 gene expression was also analyzed to determine the pluripotency of ASCs and UCSCs. The protein-protein interactions were in silico analyzed using String 9.1 software.RESULTS: Relatively, ALDH1A3 was expressed at similar level in ASCs and UCSCs, while ALDH1A1 expression level was significantly higher in ASCs compared to UCSCs. In contrast to ALDH1A3, the expressions of ALDH1A1 in both MSCs were significantly lower than breast CSCs similar to Oct-4 expressions, as also revealed by the in silico data showing the interaction between these proteins. This suggests the role of ALDH1A1 on pluripotency.CONCLUSION: ALDH1A1 and ALDH1A3 were distinctly expressed in UCSCs and ASCs, which might be associated with unique properties of ASCs and UCSCs. This study may contribute to further research in terms of implication of ALDH1A1 and ALDH1A3 expressions towards the properties of MSCs and its application in stem cell therapy.KEYWORDS: ALDH1A1, ALDH1A3, UCSC, ASC, breast ALDH+ CSC, Oct-4